Operationalized psychodynamic diagnosis as an instrument to transfer psychodynamic constructs into neuroscience - Kessler, Henrik; Stasch, Michael; Cierpka, Manfred (Frontiers in human neuroscience, 2013)
This theoretical article makes a contribution to the field of “psychoanalytically informed neuroscience”. First, central characteristics of psychoanalysis and neuroscience are briefly described leading into three epistemic dichotomies. Neuroscience versus psychoanalysis display almost opposing methodological approaches (reduction vs. expansion), test quality emphases (reliability vs. validity) and meaning of results (correlation vs. explanation). The critical point is to reach an intermediate level: in neuroscience an adequate position integrating both aspects - objective and subjective - of dual-aspect monism, and in psychoanalysis the appropriate level for the scientific investigation of its central concepts. As a suggestion to reach that level in both fields the system of Operationalized Psychodynamic Diagnosis (OPD; OPD Task Force, 2008) is presented. Combining aspects of both fields, expansion and reduction as well as reliability and validity, OPD could be a fruitful tool to transfer psychodynamic constructs into neuroscience. The article closes with a short description of recent applications of OPD in neuroscience.
Gesehen am 22.04.2021